Sample-to-Answer Droplet Magnetofluidic Platform for Point-of-Care Hepatitis C Viral Load Quantitation - Dong Jin Shin (Nature Portfolio, 2018)
Abstract Gold standard quantitative nucleic acid tests for diagnosis of viral diseases are currently limited to implementation in laboratories outside of the clinic. An instrument for conducting nucleic acid testing at the point-of-care (POC) that is easily operable by the clinician would reduce the required number of visits to the clinic and improve patient retention for proper treatment. Here we present a droplet magnetofluidic (DM) platform, which leverages functionalized magnetic particles to miniaturize and automate laboratory assays for use in the clinic at the POC. Our novel thermoformed disposable cartridge coupled to a portable multiaxial magnetofluidic instrument enables real-time PCR assays for quantitative and sensitive detection of nucleic acids from crude biosamples. Instead of laborious benchtop sample purification techniques followed by elution and spiking into PCR buffer, the user simply injects the biosample of interest into a cartridge with magnetic particles and loads the cartridge into the instrument. We demonstrate the utility of our platform with hepatitis C virus (HCV) RNA viral load quantitation from blood serum in approximately 1 hour. Clinical serum samples (n = 18) were directly processed on cartridges with no false positives and a limit of detection of 45 IU per 10 µl sample injection.